2021
DOI: 10.1002/csc2.20446
|View full text |Cite
|
Sign up to set email alerts
|

Importance of temperature in evaluating cotton for resistance to Fusarium wilt caused byFusarium oxysporumf. sp.vasinfectumrace 4

Abstract: Fusarium wilt of cotton (Gossypium spp.) is caused by a soil‐ and seed‐borne fungal pathogen Fusarium oxysporum f. sp. vasinfectum (FOV). Fusarium oxysporum f. sp. vasinfectum race 4 (FOV4) is a significant threat to cotton production in the United States. The effect of temperature and soil on disease symptoms in cultivars with a range of susceptibility to FOV4 was examined in growth chamber trials. Three upland (G. hirsutum L.) and three pima (G. barbadense L.) cultivars were planted in three types of soils (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
(67 reference statements)
3
16
0
Order By: Relevance
“…Further research should determine how blocking is best implemented (based on ranges or planting rows) in a field to reflect the distribution gradient of FOV4 inoculum density. Because of the low temperature requirement (Zhang, Abdelraheem, Dever, Nichols, Wedegaertner, Wheeler, & Zhu, 2021), plant mortality caused by FOV4 is not influenced by year‐to‐year differences in production practices (Zhang, Abdelraheem, Dever, Elkins‐Arce, Wheeler, Zhu et al., 2020). Therefore, the results obtained from the two fields each with two trials should have broad applications.…”
Section: Discussionmentioning
confidence: 99%
“…Further research should determine how blocking is best implemented (based on ranges or planting rows) in a field to reflect the distribution gradient of FOV4 inoculum density. Because of the low temperature requirement (Zhang, Abdelraheem, Dever, Nichols, Wedegaertner, Wheeler, & Zhu, 2021), plant mortality caused by FOV4 is not influenced by year‐to‐year differences in production practices (Zhang, Abdelraheem, Dever, Elkins‐Arce, Wheeler, Zhu et al., 2020). Therefore, the results obtained from the two fields each with two trials should have broad applications.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results obtained highlight a significant effect of a w , temperature, and the interactions of these factors on the radial growth of F. oxysporum isolates. Notably, the mycelial growth of isolates of different special forms of Fusarium oxysporum has been investigated in previous works [51][52][53], and the optimal temperature ranges are very similar for the different special forms studied, where the mycelial growth rate was greater at 23/26 • C. In some cases, the mycelial growth rate was not directly studied and only the manifestation of symptoms was monitored following inoculation (in different temperature ranges). There, cotton seedlings manifested more severe symptoms and higher mortality when maintained at 23 • C, followed by 20/26 • C and 29 • C in descending order [51].…”
Section: Discussionmentioning
confidence: 99%
“…The inoculum was pipetted onto the soil surface with no root wounding, and pots were lightly watered immediately after inoculation. Fungal culture, spore quanti cation, and inoculation techniques followed Zhang et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…be different, and they may have high seedling death rates Zhang et al (2020b). suggested that the low temperature conditions allow detection of high levels of qualitative FOV4 resistance, while the high temperature conditions detect low levels of quantitative resistance to FOV4 Zhang et al (2021). con rmed that FW caused by FOV4 is a temperature dependent disease with an optimal temperature of 22-23 o C to cause mortality.…”
mentioning
confidence: 99%